2010
DOI: 10.1053/j.gastro.2010.07.040
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Control Intestinal Epithelial Differentiation, Architecture, and Barrier Function

Abstract: Background and Aims While the importance of miRNA for the development and maintenance of several tissues is well established, its role in the intestine is unknown. Our aims were to determine the entire miRNA expression profile of the mammalian small intestine in a quantitative manner and to determine the contribution of miRNAs to intestinal development and homeostasis using genetic means. Methods We determined the complete miRNA transcriptome of the mouse intestinal epithelium using ultra-high throughput seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
262
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(278 citation statements)
references
References 47 publications
12
262
2
2
Order By: Relevance
“…Disruption of the intestinal barrier has been shown to be an important pathogenic mechanism contributing to the development of intestinal inflammation [22,23] . McKenna et al [24] reported that miRNAs are important for maintaining the function of intestinal barriers. miR21, which is overexpressed in chronic UC, induces the degradation of Ras homolog gene family member (Rho)B mRNA and leads to an increase in intestinal epithelial permeability due to the loss of TJ proteins and ultrastructural changes [25] .…”
Section: Mirnas and Intestinal Tissue Barriersmentioning
confidence: 99%
“…Disruption of the intestinal barrier has been shown to be an important pathogenic mechanism contributing to the development of intestinal inflammation [22,23] . McKenna et al [24] reported that miRNAs are important for maintaining the function of intestinal barriers. miR21, which is overexpressed in chronic UC, induces the degradation of Ras homolog gene family member (Rho)B mRNA and leads to an increase in intestinal epithelial permeability due to the loss of TJ proteins and ultrastructural changes [25] .…”
Section: Mirnas and Intestinal Tissue Barriersmentioning
confidence: 99%
“…As master regulators of post-transcription in cells, these regulatory miRNAs are involved in key functions in many physiological networks [21][22][23] , and differentially expression miRNAs have been implicated in the pathogenesis of diverse gastrointestinal disorders, such as cancer and inflammatory diseases [24,25] . In facts, loss of intestinal miRNAs in mouse models has been shown to impair differentiation of intestinal cells and epithelial barrier function, resulting in acute inflammation [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies implicate selected miRNAs in the development of vertebrate limbs (Hornstein et al, 2005), muscle (Chen et al, 2006;Cordes et al, 2009), heart (Zhao et al, 2007), neurons (Makeyev et al, 2007), blood Thai et al, 2007), retina (Decembrini et al, 2009) and intestine (Zeng et al, 2009). One recent study profiled miRNAs expressed in the mouse intestine and showed, through tissue-specific loss of all miRNAs, that they are necessary for epithelial barrier function (McKenna et al, 2010). More than 1000 miRNAs have been identified and some are known to sharpen spatial or temporal borders of gene expression (Stefani and Slack, 2008), but few miRNAs have well-established functions and defined target genes in tissue development and organogenesis.…”
Section: Introductionmentioning
confidence: 99%